Effect of NPK and KNO3 fertilizer on yield and quality of Madura tobacco Prancak N1 - Djajadi Djajadi; Roni Syaputra (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2019)
Madura tobacco Prancak N1 is a new superior variety with higher quality but lower nicotine content than Prancak 95 tobacco variety. The rate and form of fertilizer for the new variety has not yet been defined so that farmers have to use adding nitrogen fertilizer their tobacco with no phosphorus and potassium fertilizer. The objective of the research was to determine effect of NPK and KNO3 fertilizers on yield and quality of Madura tobacco var. Prancak N1. The research was carried out at Cen-lecen village, Pakong Sub District of Pamekasan District, Madura. The experiment was laid out in a randomized block design with three replication of each plot. Treatments consisted of 9 packs of fertilization with NPK compound fertilizer (8-15-19), and KNO3 (13-0-45) and those were compared with 1 packed of recommended using single fertilizer of 40 kg N-ZA + 36 kg P2O5-SP36 + 25 kg K2O-ZK + 5 ton organic manure per hectare. Results showed that addition of compound fertilizers NPK plus KNO3 increased absorption of macro nutrients NPK, yield and quality of madura tobacco Prancak N1 variety. Package fertilizers NPK plus KNO3 with the rate of 40 kg N + 36 kg P2O5 + 61 K2O per hectare was suggested for madura tobacco Prancak N1 variety to produce high yield (846 kg/ha), grade index value (87.4), and crop index value (73.9).